The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1097/01.mlg.0000217557.45491.bd
|View full text |Cite
|
Sign up to set email alerts
|

Functional Outcomes after CO2 Laser Treatment of Early Glottic Carcinoma

Abstract: Good oncologic results and vocal outcomes with no difference between controls and subepithelial and subligamental cordectomies support the use of CO2 laser endoscopic surgery as the first line of treatment for early glottic cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
81
2
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(86 citation statements)
references
References 14 publications
2
81
2
1
Order By: Relevance
“…Endoscopic laser cordectomy has proven to be effective in terms of local control, survival and vocal function for early glottic carcinoma [1,2] . Compared to radiotherapy laser cordectomy was found to be equal [3,4] or superior [5,6] . The advantages of laser resection include minimal bleeding, precise control of resection and the absence of postoperative edema [7] .…”
Section: Introductionmentioning
confidence: 99%
“…Endoscopic laser cordectomy has proven to be effective in terms of local control, survival and vocal function for early glottic carcinoma [1,2] . Compared to radiotherapy laser cordectomy was found to be equal [3,4] or superior [5,6] . The advantages of laser resection include minimal bleeding, precise control of resection and the absence of postoperative edema [7] .…”
Section: Introductionmentioning
confidence: 99%
“…Compared to T1RT, type III cordectomy resulted in worse outcome in terms of the GRBAS perceptive scale (especially G and B scores) and aerodynamic tests, but it was equivalent in terms of acoustic analyses and VHI. In the literature, vocal parameters after type I and type II cordectomy were not significantly different from those of normal controls [17,26]. Other studies reported that type I and type II cordectomies provided better voice quality than did type III to type V excisions [19,27,28].…”
Section: Discussionmentioning
confidence: 94%
“…Laser cordectomy was classified into 6 types after the publication of the ELS classification. Since the posttreatment voice quality can be influenced by the type of cordectomy [16,17], the surgeon should be aware of the level of voice quality that can be expected after each type of cordectomy in comparison with RT or CRT and should inform patients of these facts. To our knowledge, this is the first article to evaluate the posttreatment voice quality from subjective and objective viewpoints and to compare these results after each type of cordectomy, RT and CRT for early glottic carcinoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several Authors agree that all parameters of the GIRBAS system and VHI score have a sufficient level of reliability in clinical practice to rate different grades of dysphonia (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25).…”
Section: Discussionmentioning
confidence: 99%